Possible Drug-drug Interaction between Pregabalin and Clozapine in Patients with Schizophrenia: Clinical Perspectives - Schjerning, O.; Lykkegaard, S.; Damkier, P.; Nielsen, J. (Pharmacopsychiatry, 2015)
Introduction: Pregabalin is an antiepileptic drug with anti-anxiety properties and is approved for treatment of generalized anxiety disorder. Anxiety is common in patients with schizophrenia and pregabalin has been suggested as an off-label add-on treatment.Methods: Pregabalin was added to clozapine in 2 patients with schizophrenia, who both suffered from severe anxiety symptoms.Results: Both patients experienced falls and consequently bone fractures. Increased plasma levels of clozapine likely contributed to the outcome. One patient had confirmed seizures whereas the mechanism in the other patient was less clear.Discussion: This short report discusses the possible mechanism of a pregabalin-clozapine interaction.
Keywords: pregabalin; clozapine; side effects; schizophrenia; anxiety